2015
DOI: 10.1051/0004-6361/201424838
|View full text |Cite
|
Sign up to set email alerts
|

Updated census of RR Lyrae stars in the globular clusterωCentauri (NGC 5139)

Abstract: Aims. ω Centauri (NGC 5139) contains many variable stars of different types and, in particular, more than one hundred RR Lyrae stars. This enabled gathering a homogeneous sample (in terms of instrument, image quality, and time coverage) of high-quality near-infrared (NIR) RR Lyrae light curves by performing an extensive time-series campaign aimed at this object. We have conducted a variability survey of ω Cen in the NIR, using ESO's 4.1 m Visible and Infrared Survey Telescope for Astronomy (VISTA). This is the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 61 publications
(129 reference statements)
6
71
0
Order By: Relevance
“…In this diagram we can see that our RR Lyrae stars are predominantly Oosterhoff Type I (OoI) with a minor composition of Oosterhoff Type II (OoII). We derived this composition with the Oosterhoof reference lines traced by Navarrete et al (2015). In addition to the period and amplitude, another characteristic feature of the RRab stars is the light curve shape, which can be described by a Fourier series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this diagram we can see that our RR Lyrae stars are predominantly Oosterhoff Type I (OoI) with a minor composition of Oosterhoff Type II (OoII). We derived this composition with the Oosterhoof reference lines traced by Navarrete et al (2015). In addition to the period and amplitude, another characteristic feature of the RRab stars is the light curve shape, which can be described by a Fourier series.…”
Section: Resultsmentioning
confidence: 99%
“…In our catalog there are eight matches within d < 1 in tiles b220 and b221. Three of the five remaining RRab stars were not analyzed by our algorithm owing to non-stellar photometry flags or fewer epochs than the minimum required, and there were no matches at 1 for Navarrete et al (2015) are shown. Bottom panel: period histogram of the 1019 RRab stars with bins adapted by the Bayesian Block algorithm (Scargle et al 2013) through the astroML implementation (Vanderplas et al 2012).…”
Section: Detection and Classification Of Rr Lyrae Starsmentioning
confidence: 99%
“…They provided homogeneous JK s photometry for 180 variables and provided a new estimate of the ω Cen distance modulus using the K-band PL relation (13.77 ± 0.07 mag). A similar analysis was recently performed by Navarrete et al (2015) based on a large set of images collected with the VISTA telescope. They provided homogeneous JK s photometry for 189 probable member RRLs (101 RRc, 88 RRab) and discussed the pulsation properties of the entire sample in the NIR.…”
Section: Introductionmentioning
confidence: 87%
“…All of the known variables are outside the field of view of our reference image. Most recently, Navarrete et al (2015) made an updated analysis of the variables in this cluster, but the variables in their study are also located outside the field of view of our reference image.…”
Section: Known Variablesmentioning
confidence: 99%